The relationship between critical thinking dispositions and academic achievement in Iranian midwifery students - Mahin Tafazzoli; Farzaneh Rashidi Fakari; Mahjoobeh Ramazanzadeh; Abdolazim Sarli (Tehran University of Medical Sciences, 2016)
Background & Aim: Students' academic achievement is one of the important indicators in the assessment of higher education. Applying critical thinking in education is a significant factor affecting the growth and development of the students. This study was performed in an attempt to determine the relationship between critical thinking dispositions and academic achievement in midwifery students of Mashhad University of Medical Sciences, Iran, in 2014. Methods & Materials: This correlation study was conducted on 60 midwifery students of Mashhad School of Nursing and Midwifery in 2014. All eligible students were recruited in this study. Data collection instruments included demographic and academic achievement form and the California Critical Thinking Disposition Inventory. Collected data were analyzed by descriptive statistics tests and Pearson correlation coefficient using SPSS software version 16. Results: The mean and standard deviation (SD) of the total score of critical thinking dispositions were 260.10 ± 38.18. The mean (SD) grade point average of students was 16.31 ± 1.05. The results of Pearson correlation test showed no significant relationship between the total and subscales scores of critical thinking and academic achievement (P > 0.05). Conclusion: The results of this study indicated that there was no significant relationship between the critical thinking dispositions and its subscales with academic achievement.